NEW PRIMORDIAL MAGNETIC FIELD EVOLUTION AND SIGNATURE ON THE CMB SPECTRUM (Journal of Sciences & Technology, 2016)
A new scenario for a primordial magnetic field is proposed and its evolution is presented. Signatures on the cosmic microwave background spectrum are also discussed.